Nursing students knowledge about Isolation and quarantine. - حسين, ناهد (Latakia University Journal -Medical Sciences Series, 2022)
Isolation and quarantine represent the most important measures for controlling inflammation, and students of the College of Nursing represent an important social segment that needs to be provided with correct knowledge about these two measures, in order to be able to practice them and provide awareness about their application in the community. Therefore, this research aims to evaluate the knowledge of students of the Faculty of Nursing at Tishreen University about Isolation and quarantine. Where the sample included 200 students from the third and fourth years, who were selected by the convenient sample method, and data were collected using a questionnaire form developed by the researcher. The results showed that 78% of students had good knowledge about quarantine, and 90% had good knowledge about Isolation. The study recommended strengthening the knowledge of students of the College of Nursing on how to apply quarantine to large gatherings and the procedures to be followed when isolating parents and children together, developing an informational guide explaining the procedures and precautions for isolation and quarantine, and conducting similar research on a larger scale and including the rest of the medical colleges.